Combined laparoscopic and robotic surgery for synchronous colorectal and genitourinary cancer: A case series. (2018) - Imagami, Toru; Takayama, Satoru; Hattori, Taku; Matsui, Ryohei; Sakamoto, Masaki; Kani, Hisanori; Kurokawa, Satoshi; Fujiwara, Tsuyoshi
Highlights: Combined laparoscopic and robotic surgery for synchronous colorectal and genitourinary cancer are extremely rare. In simultaneous endoscopic surgery, it is necessary to decide sequence of resection, intraoperative patient's position and port arrangement. Combined laparoscopic and robotic surgery is suitable for advanced cancer cases requiring multidisciplinary treatment. Abstract: Introduction: Advances in diagnostic techniques and treatment have resulted in an increase in patients with synchronous cancer. Surgical reports of combined laparoscopic and robotic resection for synchronous colorectal and genitourinary cancer are rare. Materials and methods: Between August 2015 and November 2017, three patients underwent combined laparoscopic and robotic surgery for synchronous colorectal and genitourinary cancer in our hospital. Results: Case 1 was a 59-year-old man with synchronous rectal and prostate cancer treated by combined laparoscopic anterior resection and robotic-assisted prostatectomy. Case 2 was a 77-year-old man with synchronous cancer of transverse colon and left kidney treated by combined laparoscopic transverse colectomy and robotic-assisted partial nephrectomy. Case 3 was a 74-year-old man with synchronous adenocarcinoma of descending colon and prostate treated by combined laparoscopic left hemicolectomy and robotic-assisted prostatectomy. Discussion: In simultaneous endoscopic surgery, it is necessary to consider sequence of resection, intraoperative position of patient and port arrangement. Simultaneous surgery allows promptly for postoperative adjuvant chemotherapy. Conclusion: Combined laparoscopic and robotic surgery for synchronous colorectal and genitourinary cancer is suitable for advanced cancer cases requiring multidisciplinary treatment.